A randomized controlled trial of surface neuromuscular electrical stimulation applied early after acute stroke: effects on wrist pain, spasticity and contractures. (July 2013) - Malhotra, Shweta; Rosewilliam, Sheeba; Hermens, Hermie; Roffe, Christine; Jones, Peter; Pandyan, Anand David
Objectives: To investigate effects of surface neuromuscular electrical stimulation applied early after stroke to the wrist and finger extensor muscles on upper limb pain, spasticity and contractures in patients with no functional arm movement. Design: Secondary analysis from a Phase II, randomized, controlled, single-blind study. Setting: An acute hospital stroke unit. Subjects: Patients with no useful arm function within six weeks of a first stroke. Intervention: Patients were randomized to treatment (30-minute sessions of surface neuromuscular stimulation to wrist and finger extensors and 45 minutes of physiotherapy) or control (45 minutes of physiotherapy) groups. All patients had access to routine care. Treatment was given for six weeks from recruitment. Results: Ninety patients (49% male, median age 74 years (range 32–98), median time since stroke onset three weeks (range one to six weeks)) were included. Treatment compliance was variable (mean 28%). The treatment prevented the development of pain (mean difference in rate of change 0.4 units/week, 95% confidence interval (CI) 0.09 to 0.6). Treatment may have prevented a deterioration in contractures (quantified by measuring passive range of movement) in severely disabled patients (mean rate of deterioration −0.5 deg/week; 95% CI −0.9 to −0.06). There were no significant changes in stiffness and spasticity. Conclusion: Surface neuromuscular electrical stimulation reduces pain in stroke patients with a non-functional arm. There was some evidence that treatment with electrical stimulation was beneficial in reducing contractures. Treatment had no effect on spasticity.